The tale of the rattle: Using rattle size to understand growth and sexual dimorphism in an insular population of rattlesnakes (Crotalus oreganus caliginis) - Roman A. Nava; José Jesús Sigala‐Rodríguez; Nathaniel Redetzke; Ivan Villalobos‐Juarez; Cristian Franco‐Servin‐de‐la‐Mora; Ramses Rosales‐García; Rulon W. Clark (Ecology and Evolution, 2024)
Abstract Islands have played a key role in our understanding of rapid evolution. A large body of literature has examined morphological changes in response to insularity and isolation, which has yielded useful generalizations about how animals can adapt to live in very small geographic areas. However, understanding the evolution of morphological variation in insular populations often requires detailed data sets on longitudinal patterns of growth and development, and such studies typically necessitate long‐term mark‐recapture on a large sample of individuals. Rattlesnakes provide a unique opportunity to address some of these difficulties because the addition of rattle segments to the rattle string occurs with regular periodicity and their size directly correlates with the body size of the snake at the time of the ecdysis cycle generating the segment. Here, we used a large database of rattle segment sizes recorded from island (Isla Coronado Sur, Baja California, Mexico) and mainland (Camp Pendleton, California, United States) populations of Western Rattlesnakes (Crotalus oreganus and C. o. caliginis) that separated approximately 10,000 years ago to compare body sizes at different ecdysis cycles, which allowed us to assess differences in growth rates and patterns of sexual size dimorphism. Our results show that rattlesnakes on Isla Coronado Sur appear to be born smaller and grow more slowly than their mainland counterparts, resulting in a “dwarfed” island population. However, despite significant differences in body size, both populations exhibited the same degree of sexual dimorphism. Our study demonstrates the potential to use rattle characteristics to recover detailed estimates of fundamental demographic parameters.